A Fly on the Wall: How Stress Response Systems Can Sense and Respond to Damage to Peptidoglycan - Delhaye, Antoine; Collet, Jean-François; Laloux, Géraldine (Frontiers in Cellular and Infection Microbiology, 2019)
The envelope of Gram-negative bacteria is critical for survival across a wide range of environmental conditions. The inner membrane, the periplasm and the outer membrane form a complex compartment, home to many essential processes. Hence, constant monitoring by envelope stress response systems ensure correct biogenesis of the envelope and maintain its homeostasis. Inside the periplasm, the cell wall, made of peptidoglycan, has been under the spotlight for its critical role in bacterial growth as well as being the target of many antibiotics. While much research is centered around understanding the role of the many enzymes involved in synthesizing the cell wall, much less is known about how the cell can detect perturbations of this assembly process, and how it is regulated during stress. In this review, we explore the current knowledge of cell wall defects sensing by stress response systems, mainly in the model bacterium Escherischia coli. We also discuss how these systems are able to respond to cell wall perturbations in order to increase fitness, and what implications this has on cell wall regulation.